Phosphate-induced Stimulation of Acceptorless Respiration in Corn Mitochondria - Hanson, J. B. (1972)
By use of the organic mercurial mersalyl to block phosphate transport, it has been shown that only a small fraction of the respiratory increase of corn mitochondria in response to additions of inorganic phosphate is due to energy expended in phosphate accumulation. Most of the respiratory release occurs from accelerated turnover of the coupling mechanism with internal phosphate in an oligomycin-sensitive reaction. Addition of ADP to mersalyl-blocked mitochondria depletes internal phosphate in ATP formation and respiration declines. Arsenate produces the same responses as phosphate but is more effective in respiratory release. Inhibition of the ADP-ATP antiporter with atractyloside shows that the increased respiration with internal phosphate is not due to turnover of ADP acceptor through exogenous ATPase. Use of valinomycin to facilitate movement of K(+) greatly accelerates the rate of phosphate swelling, but there is no consistent correlation between respiration and swelling. In the absence of phosphate, valinomycin dramatically releases respiration with only trivial swelling. The data indicate that loose coupling in due only fractionally to energy expenditure in ion transport. An explanation consistent with the observations can be derived by assuming that both a high energy intermediate (I ∼ X) and a proton motive force—or its electrochemical equivalent—arise at coupling sites.